THE ANALISYS OF STUDENTS’ DIFFICULTIES IN ACCOMPLISHING TOEFL MINIMUM SCORE AS THE FINAL REQUIREMENT - Indah Fadhilah Rahman; Kamsinah Kamsinah; Nur Aliyah Nur (ETERNAL (English, Teaching, Learning and Research Journal), 2021)
: Uin Alauddin Makassar The research aimed to find out the difficulties that encountered by the students in answering the TOEFL, and to find out the strategies that can be applied in order to help students overcome their difficulties in TOEFL. This research applied descriptive research with qualitative approach as the data were analyzed qualitatively. This research was conducted in English Education Department in Tarbiyah and Teaching Training Faculty of UIN Alauddin Makassar with 40 subjects of the sixth to eight semester students of English Education Department by using purposive sampling. The data were collected by using opened-questionnaire. the researchers found that there were three kinds of difficulties encountered by students in answering the TOEFL test namely, (1) fewer basic skills in answering the TOEFL test, (2)  the students’ less practice, and (3) the students’ lack of motivation in studying the skills of TOEFL test. In addition, there were some strategies that the students used when they encountered difficult question in answering the TOEFL test such as: (1) skipping the difficult items and focusing on the easier items, (2) thinking hard and usually spending so much time in one question, (3) thinking hard and effort to spend short time in one question, (4) and guessing. Through this research, it is suggested to the institution to conduct TOEFL preparation course and well-manageable TOEFL administration.